Estimation of global rating changes in quality of life and marital satisfaction among reproductive age women in Iran and Afghanistan before and after COVID-19 pandemic - Masomeh Khalili; Shahideh Jahanian Sadatmahalleh; Malihe Nasiri; Ali Montazeri (BMC, 2023)
Abstract Background Quality of life and marital satisfaction are important components of reproductive-age women's health. This study aimed to compare the quality of life and marital satisfaction in women of reproductive age in Iran and Afghanistan before and after the COVID-19 pandemic. Methods This was a cross-sectional study on a sample of Iranian and Afghan women of reproductive age. To collect the data, the 12-item short-form health survey (SF-12) and the Enrich marital satisfaction scale were used to assess the quality of life and marital satisfaction, respectively. In addition, the Global Rating of Change (GRC) was used in order to evaluate the quality of life and marital satisfaction compared to before the COVID-19 pandemic. Data were evaluated descriptively through statistics including sing t-test, and chi-square, Logistic regression was performed to assess the relationship between outcome variables and independent variables. Results In all 599 reproductive-age women (300 Iranian, and 299 Afghan) were studied. After adjusting for demographic variables, no significant difference was observed between the two groups for the physical component (P = 0.05) and mental component summary scores of quality of life (P = 0.166) as measured by the SF-12. The majority of Iranian women reported that their quality of life was worsened compared to before the pandemic (57.2%), while in the Afghan group, a higher percentage declared that it was unchanged (58.9%). The mental component of quality of life had no significant relationship with any of the independent variables including nationality. In contrast, the physical component quality of life had a significant relationship with nationality (P = 0.01). Iranian women had more marital satisfaction than Afghan women (P<0.001) and marital satisfaction had a significant relationship with nationality (P<0.001). Most women in both groups (70% of Iranian and 60% of Afghan women) declared that their marital satisfaction unchanged compared to before the COVID-19 pandemic. Conclusion The results showed that the quality of life of Iranian and Afghan women of reproductive age was almost the same before and after the pandemic. However, Iranians scored lower on the mental component summary and Afghans reported lower scores on the physical component summary. Marital satisfaction of Afghan women was much lower than that of Iranian women. The findings suggest the need for serious attention by health care authorities. Providing a supportive environment might be considered a primary step towards a better quality of life for these populations.